(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This research aims to study the importance of the role of Islamic religious education in facing global challenges of modern humanity (environmental conservation), especially at the high school level. This research also tries to find out whether or not there is an element of fiqh bi’ah in Islamic religious education and ethics for senior high school students, and whether innovative solutions should be made by Islamic education teachers in responding to fiqh bi’ah elements in the independent curriculum (kurikulum Merdeka). This is qualitative research, and the data collection techniques include documentation and description. The data are analyzed using content analysis for processing information more deeply in the form of writing, news, and images. The final results show that in kurikulum Merdeka, the Islamic education and characteristics already contain elements of bi’ah fiqh (in subject objective). However, there are fewer elements of bi’ah fiqh in the learning outcomes in phases E and F. Likewise, in the Islamic education (PAI) and character education (BP) textbooks for grades 10, 11, and 12 senior high school students, there are no fiqh bi’ah elements. This issue can affect the educators in preparing annual programs, semester programs, the flow of learning objectives, indicators of achievement of learning objectives, and teaching modules which also do not include elements of fiqh bi’ah.